2011
DOI: 10.4103/0301-4738.83613
|View full text |Cite
|
Sign up to set email alerts
|

Mycotic corneal ulcers in upper Assam

Abstract: Purpose:To study the association of various risk factors and epidemiological variables of mycotic keratitis treated at a tertiary referral hospital of upper Assam.Materials and Methods:In this hospital-based prospective study a total of 310 consecutive corneal ulcer cases attending the ophthalmology outpatient department of Assam Medical College were enrolled between April 2007 and March 2009. After clinical and slit-lamp biomicroscopic examination in all suspected cases, smears and culture examination for fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 10 publications
4
44
0
3
Order By: Relevance
“…the findings were closely corroborated with the study of Reema Nath et al which revealed 87.9% rural and 11.5% urban population involved in their study. (3) As represented in figure 2, it establishes that culture positivity was more with advancement of age as immunity tend to decrease with old age, thereby facilitating growth of pathogens yielding more culture positivity and the observations closely corroborated with the studies by Gulnaz Bashir et al, M Jayahar Bharathi et al and Khokar N. et al (1,4,5) The overall male:female ratio is 1.54:1. The observations revealed that in both bacteriological and fungal aetiologies of ocular infections, the males were more affected than females; the male preponderance may be due to more exposure to external environment in comparison to females.…”
Section: Discussionsupporting
confidence: 80%
“…the findings were closely corroborated with the study of Reema Nath et al which revealed 87.9% rural and 11.5% urban population involved in their study. (3) As represented in figure 2, it establishes that culture positivity was more with advancement of age as immunity tend to decrease with old age, thereby facilitating growth of pathogens yielding more culture positivity and the observations closely corroborated with the studies by Gulnaz Bashir et al, M Jayahar Bharathi et al and Khokar N. et al (1,4,5) The overall male:female ratio is 1.54:1. The observations revealed that in both bacteriological and fungal aetiologies of ocular infections, the males were more affected than females; the male preponderance may be due to more exposure to external environment in comparison to females.…”
Section: Discussionsupporting
confidence: 80%
“…The observation that younger male farmers are at higher risk for fungal keratitis has been made by a number of other authors in different countries. 11,13,[22][23][24][25][26] Significantly higher numbers of younger males were affected in the tropical and rural/regional areas of Queensland, where agriculture remains an important economic activity. While we did not collect data on occupation, younger males are more likely to be involved in agriculture, as well as other outdoor work.…”
Section: Discussionmentioning
confidence: 99%
“…13 In India, Fusarium species have been reported to be the most common causative agents of fungal keratitis. 3,14,15 There is an urgent need to expand our knowledge of these species in terms of epidemiology, methods of prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%